Крижанич и Караджич: в поисках метаязыковых решений - Дмитриевич Дуличенко, Александр (Slavistica Vilnensis, 2000)
The article compares two linguistic strategies for the creation of standard (literary) languages, those of Juraj Križanić (1617/1618–1683) and Vuk Karadžić (1787–1864). As a typical representative of his age, J. Križanić designed an abstract linguistic system meant to form the base for a common Slavic language (ruski jezik or vseslavjanskij jazyk, in his terms), based on a number of Slavic languages or dialects. V. Karadžić, a representative of 19th-century linguistics and the founder of the Serbian literary language, proceeded in a different way: he singled out one dialect basis for the future standard language and then supplemented it with elements from other dialects of the same language.